Aggregation behavior of self-assembled nanoparticles made from carboxymethyl-hexanoyl chitosan and sodium dodecyl sulphate surfactant in water - Agudelo, Alvaro J. P.; Silva, Luis H. M. da; Rengifo, Andrés F. C.; Santos, Sandra C.; Lima, Vania R. de; Parize, Alexandre L.; Minatti, Edson (Journal of Molecular Liquids, 2019)
Biopolymers can be used to produce nano-objects in solution and they are generally of low cost and biocompatible. However, they commonly have low kinetic stability and form aggregates with a broad particle size distribution, characteristics that hinder their use in drug delivery systems. Herein, we report the thermodynamics and mechanisms underlying the formation of nanostructures through the self-assembly of carboxymethyl-hexanoyl chitosan (ONCHC) and the effect of the presence of the surfactant sodium dodecyl sulfate (SDS). The pre- and post-aggregation regimes were monitored using several techniques and indicated that self-assembly is thermodynamically favorable. The presence of SDS decreased the hydrodynamic radius and surface charge of the SDS-ONCHC nanoaggregates and increased the kinetic stability in aqueous solution over a period of 150 days. The SDS-ONCHC interaction is driven mainly by a hydrophobic effect and the addition of SDS increases the number and strength of the hydrophobic domains, where the integral enthalpy change for the aggregate formation is −2.11 kJ mol−1.
Keywords: Carboxymethyl-hexanoyl chitosan; Polymer surfactant complex; Isothermal titration calorimetry (ITC); Conductivity; Dynamic light-scattering (DLS); Surface tension